Improvement of power transfer efficiency of hexagonal coil arrays in misalignment conditions - Sianturi Tigor Franky Devano; Taufik Hidayat; Mudrik Alaydrus (Institute of Advanced Engineering and Science, 2021)
Wireless charging by transferring energy between two objects using electromagnetic fields commonly called Wireless power transfer is an alternative technology that is physically installed in an electric vehicle (EV) to charge. Parking alignment is a very important factor in driver behavior that affects Power transfer efficiency (PTE). The proposed hexagonal coil array design in this experiment is to optimize PTE and receiver coil size. The experimental results show that PTE in the tangential boundary plane Misalignment increases by 5-10% when compared to coil array circles and increases by 82% when compared to single coil circles.